Fundamentals of Language and Language Learning: A Collaborative Initiative for the Implementation of a Common Online Language Training Component in the First-Year Language Curriculum - Barysevich, Alena; Smeets, Liz (Nouvelle Revue Synergies Canada)

(untitled) (University of Guelph, School of Languages and Literatures, 2021)
The Fundamentals of Language and Language Learning is an online mini course developed at the School of Languages and Literatures (University of Guelph). The four online modules are integrated in the core curriculum of all introductory language courses and are mandatorily completed by an incoming cohort of all first-year language students. This cross-subjects and cross-departmental project addresses the educational challenges students face as they transition from high school to university and offers a more general, rich, yet linguistically supported language learning training. The 10-15 hours of asynchronous autonomous work equip students with a toolbox for effective language learning in a second/foreign language classroom. Students explore how languages are structured, function, change, interconnected with each other and how they could use this knowledge for faster, easier, more effective, and more sustainable language learning. The mini course empowers the second/foreign language learner through activating earlier acquired languages and by applying fundamentals of linguistics into the process of language learning.